Which causal relationships can reject or accept the significant optimum distribution ratios phases in the triple jump - Zerf, M.; Mokkedes, M. I.; Biengoua, A.; Bendahmane, M. N. (American Journal of Sports Science, 2015)
The objectives of this study were to detect some causal relationships in significant differences optimum distribution ratios phases that the most sources agree that it varies from athlete to the other. Our subjects were the finalists (2009-2011) with Hop-dominated technique, 17 meter as minimum performance and the best performance in the world triple Jump with Jump-dominated technique, 18 meter as minimum performance in other comparison. In the absence of technological means in Algeria, our study explores the reports (IAAF) in order to answer: Which causal relationship explained or dismissed the Optimum distribution ratios phases in the two-practiced dominant technique (Hop and Jump) to achieve results? For this, we chose the analysis of the Regression to be compared, the impact phase distributions (hop, step and jump) charged with the results achieved in their test. Our goal for this research is: Improve search through the Optimum use of data results champions. Find a causal relationship between dominant technique and results as research topic in Optimum ratios phases. The most important results obtained: Optimum distribution ratios phases in the hop-dominated technique varies from athlete to other because the respect of the model theories Russian requires the Stride length of the three phases typically to (39%: 30%: 31%).Optimum distribution ratios phases in the jump-dominated technique should be us as optimum phase ratio in condition that the Stride length of the three phases typically to (34%29%37%).